A clinical profile of compulsive exercise in adolescent inpatients with anorexia nervosa. Issue 1 (December 2016) - Noetel, Melissa; Miskovic-Wheatley, Jane; Crosby, Ross; Hay, Phillipa; Madden, Sloane; Touyz, Stephen
Abstract Background The aim of the current study was to contribute to the development of a clinical profile of compulsive exercise in adolescents with Anorexia Nervosa (AN), by examining associations between compulsive exercise and eating and general psychopathology. Method A sample of 60 female adolescent inpatients with AN completed a self-report measure of compulsive exercise and a series of standardized self-report questionnaires assessing eating and general psychopathology. Results Higher levels of compulsive exercise were associated with increased levels of eating disorder psychopathology and anxiety. Specifically, the avoidance aspect (negatively reinforced) of compulsive exercise was associated with elevated scores on measures of eating disorder, anxiety, depression, and obsessive compulsiveness psychopathology, as well as lower self-esteem scores. The mood improvement value (positively reinforced) of compulsive exercise, however, did not reflect such trends. Conclusions Compulsive exercise driven by avoidance of negative affect is associated with more severe psychological features in adolescent inpatients with AN. The current findings emphasize the need for research and clinical efforts in the development of treatments addressing avoidance of negative affect and compulsive exercise in adolescents with AN.